Correlations of Organizational Justice and Professional Commitment with the Demographic Variables of Nurses - F Rakhshany Zabol; O Akbari; F Kiani; F Sarhadi (Iran University of Medical Sciences, 2019)
Background & Aims: Nurses are the primary agents in patient care, who are in direct contact with patients. In addition to persistence in the nursing profession and job satisfaction, professional commitment could enhance patient safety and quality of patient care. The present study aimed to assess the correlations between organizational justice and professional commitment with the demographic variables of nurses in the teaching hospitals affiliated to Zahedan University of Medical Sciences, Iran in 2018. Materials & Methods: This descriptive-correlation study was conducted on 298 nurses, who were selected via stratified sampling from the hospitals in Zahedan, Iran. Data were collected using Lin's nurses' professional commitment scale and Moorman and Niehoff's organizational justice questionnaires. Data analysis was performed in SPSS version 21 using one-way analysis of variance (ANOVA), independent t-test, and Pearson correlation-coefficient at the significance level of 0.05. Results: The mean scores of professional commitment and organizational justice were 3.68 ± 0.55 and 3.97 ± 1.52, respectively. In addition, the results of Pearson's correlation-coefficient showed a positive, significant correlation between the variables of organizational justice and nurses professional (P<0.001; r=0.23). The mean scores of nursing cognition (P=0.01) and persistence in the nursing professionals (P=0.03) were significantly higher in male nurses compared to the female nurses. Moreover, persistence in the nursing profession was significantly higher in married nurses compared to the single nurses (P=0.02). The mean score of total organizational justice and the dimensions of distributive justice and interactional justice were significantly higher in the male nurses compared to the female nurses (P<0.05). However, no significant correlation was observed between organizational justice and its dimensions with marital status (P>0.05). Conclusion: Healthcare system managers could develop and implement interventions to increase the perceived organizational justice of nurses, especially in the terms of distributive justice, in order to improve the professional commitment of these healthcare professionals and improve the quality of nursing care.